Migrating Literatures: Bulgaria in the American Imaginary - Alexandra Glavanakova (European Journal of American Studies)
One of the most intriguing areas for comparative research in contemporary cultural studies and world literature(s) is the interrelation between cultural identity and the imagination. This article aims to focus on the perceptions and representations of Bulgaria in the American cultural imaginary. To fulfill this goal, I examine critical and fictional transatlantic readings of Bulgaria through American eyes, focusing on the following questions: How are conflicts of identity thematized and represented in imaginary creative outputs, which reflect on the construction of the “West” and the “East,” of Self and Other, of “Europeanness” (“Balkanness”) and “Americanness”? Bulgaria emerges not only as a setting for the action in fictional works written by U.S. writers, but also as a sub-text rich in implications and references, as demonstrated by four novels: Elizabeth Kostova’s The Historian and The Shadow Land and Garth Greenwell’s What Belongs to You and Cleanness, which are the focus of analysis.